Can the Global Forest Sector Survive 11°C Warming? - Alice Favero; Robert Mendelsohn; Brent Sohngen (Fondazione Eni Enrico Mattei (FEEM), 2017)
It is well known that the forestry sector is sensitive to climate change but most studies have examined impacts only through 2100 and warming of less than 4°C. This is the first timber analysis to consider possible climate change impacts out to 2250 and warming up to 11°C above 1900 levels. The results suggest that large productivity gains through 2190 lead to a continued expansion of the global timber supply. However, as carbon fertilization effects diminish and continued warming causes forestland to continue to shrink, warming above 8°C is predicted to become harmful to the forest sector.
Keywords: Q5; Q23; 330; Climate change; RCP 8.5; Forestry; Dynamic optimization; Timber market